Umidaxon THE CULTURAL ANALYSIS OF SOME ENGLISH PROVERBS WITH THE CONCEPT KNOWLEDGE: THE CULTURAL ANALYSIS OF SOME ENGLISH PROVERBS WITH THE CONCEPT KNOWLEDGE - Chorshanbiyeva, Umidaxon (Журнал иностранных языков и лингвистики, 2022)
This paper is devoted to the analysis of semantic features of some English and Uzbek proverbs about knowledge. The equivalents of some proverbs in a target language are given for interpreting them in the other language to find out several important innovative ways of translation and contrasting their peculiarities in the English and Uzbek languages. The results and examples of this paper can help to distinguish some differences in the meanings of the English and Uzbek proverbs about knowledge and to learn linguocultural peculiarities of them.